Effects of low frequency ultrasound pretreatment on anaerobic digestion of sludge - Mao, Taohong (2010)
Arising from escalating wastewater sludge quantity and disposal cost, research work has been initiated to explore improvement of sludge digestion through pretreatment techniques. Amongst possible pretreatment methods, sonication treatment exhibits a greater potential for being environmentally and economically sound. However, many aspects pertaining to this ultrasound pretreatment, such as the optimal operating conditions, the influence of pretreatment on bioconversion process, the feasibility of sonicated sludge for continuous anaerobic digestion and the mechanism of sludge sonication, have not been explored in much detail.